BIAS PATRIARKI DI BALIK PELAKSANAAN TRADISI TUNDUAK DI MINANGKABAU - Silvia Rosa (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2021)
In Minangkabau society, the Tunduak is a tradition when the newly marriage visits father in law's house for the first time. This article aims to discuss the meaning of implementing the Tunduak Tradition carried out by the bride in Solok Regency, West Sumatra Province. The research method used is a cognitive semiological methods. Data were collected through field surveys in photographs and words or narration obtained through audio and visual recording techniques. Data analysis was performed using the semiotic theory of myth by Rolland Barthes. The implementation of this tradition is accompanied by members of the bride's relatives who come with various kinds of luggage to be presented to the groom's relatives. The study results show that the implementation of the Tunduak Tradition in the view of the Minangkabau custom in Solok Regency gives its characteristics in Minangkabau customs' performance. Namely the accompaniment of the group's configuration walking to the house of the bride's parents-in-law while carrying the luggage placed on the head, and only done by the woman's close relatives of the bride. It reflects a cultural parade that can be used as an exciting spectacle in various areas in Solok Regency. The study results concluded that the implementation of the Tunduak Tradition represents an institutionalized myth to glorify the position and position of men in the matrilineal society in Minangkabau.